Analisis Tenaga Kerja Penjual Melalui Pembagian Area Kerja Pemasaran pada PT. Langgeng Jaya Plastindo - Rahayu, Wulan; Sukaris, Sukaris (Al-Amien Prenduan for Islamic Institute, 2024)
The important role of the plastic recycling industry which continues to grow requires an optimal marketing strategy so that it remains in demand by customers and is not less competitive with other similar companies. In an effort to increase sales efficiency and effectiveness, division of work areas was implemented and the company realized the need for an in-depth analysis of its sales workforce. The aim of this research was to determine the impact of division of marketing work areas on the workforce. This research approach uses descriptive qualitative research with the research object being PT employees. Langgeng Jaya Plastindo. The results of this research show that dividing marketing work areas is one of the main strategies for maximizing the potential of each sales team member to be more focused on achieving the set targets. The cause of the problem here is that there is no clear structure regarding the division of marketing areas, so that some areas have the potential to be unreachable or neglected. This is also caused by the unequal distribution of work areas and workforce.